Enhancing Arabic Language Writing Skills Using Khut Iqra' wa Tarjim Application as an Evaluation Tool - Syaputra, Oka; Rachmawati, Miatin (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Research was carried out to find out the effectiveness of Khut Iqra’ wa Tarjim, an evaluation tools for writing skills in Arabic language lessons. The research model used was a one-group pretest-posttest design. The sampling technique used was saturated sampling, with 13 students in senior high school as samples. The pre-test and post-test that the researchers applied were to give the student a test of their writing skills. The data obtained was then analyzed using quantitative descriptive techniques with the help of IBM SPSS Statistics 25 on samples. The analysis carried out to determine the level of effectiveness of this study is the T test and the effectivity test, or N-Gain. Analysis of the use of Khut Iqra’ wa Tarjim games as a daily evaluation tool in Arabic language learning for students shows that there is a real difference between before and after treatment. Therefore, the novelty of this research, namely, learning Arabic using the learning medium of Khut Iqra’ wa Tarjim as an evaluation tool, is very effective in improving student writing skills in Arabic learning.